The Truth of iek - Bowman, Paul (Bloomsbury Publishing, 2007)
Žižek, Slavoj is widely regarded as one of the world''s most important contemporary thinkers. His work has contributed dramatically to the reinvention and revivification of many key theoretical and political debates. Indeed, his vociferous and challenging body of work amounts to a sustained, ground-breaking, terrain-shifting and far reaching intervention into a large number of academic disciplines, intellectual fields and cultural debates. The Truth of Žižek, Slavoj addresses the rigorous critical assessment demanded by this broad and increasingly influential corpus. This timely and compelling collecti.